Ethoxylated amine friction modifiers and ZDDP - Dawczyk,J; Russo,J; Spikes,H (Tribology Letters, 2019)
The influence of a series of Ethomeens (ethoxylated alkylamine organic friction modifiers) on the durability and friction of tribofilms formed by a commercial blend of primary and secondary ZDDP in sliding/rolling contact has been studied. When pre-formed ZDDP tribofilms are rubbed in Ethomeen solution, boundary friction is reduced and some of the ZDDP film is removed. Ethomeens having just two ethoxy groups give lower boundary friction on ZDDP than those with 15 ethoxy groups, but result in much greater removal of the tribofilm itself. Based on XANES analysis, the film removed by both types of Ethomeen consists primarily of nanocrystalline orthophosphate. The level of boundary friction and its dependence on sliding speed, coupled with the dimensions of the molecules, suggests that the Ethomeens with two ethoxy groups may form quite closely packed vertical monolayers on ZDDP tribofilm surfaces, but that those with fifteen ethoxy groups cannot be close packed; yet they still reduce boundary friction significantly. The study shows that selection of an appropriate aminic friction modifier for use with ZDDP is a balance between its ability to reduce friction and its potentially harmful effect on a ZDDP tribofilm.